Effects of probiotics (cultured Lactobacillus subtilis/Streptococcus faecium) in the treatment of alcoholic hepatitis. Issue 11 (November 2015) - Han, Sang Hak; Suk, Ki Tae; Kim, Dong Joon; Kim, Moon Young; Baik, Soon Koo; Kim, Young Don; Cheon, Gab Jin; Choi, Dae Hee; Ham, Young Lim; Shin, Dong Hoon; Kim, Eun Ji
<x xml:space="preserve">Abstract</x> Background Probiotics might reduce gut-derived microbial lipopolysaccharide (LPS) by restoring bowel flora in patients with alcoholic hepatitis (AH). We evaluated the therapeutic effects of probiotics in patients with AH. Patients and methods Between September 2010 and April 2012, 117 patients (probiotics 60 and placebo 57) were prospectively randomized to receive the 7 days of cultured Lactobacillus subtilis/Streptococcus faecium (1500 mg/day) or placebo. All patients were hospitalized and were not permitted to consume alcohol for the 7 days of the study. Liver function test, proinflammatory cytokines, LPS, and colony-forming units by stool culture were examined and compared after therapy. Results In both groups, the mean levels of aspartate aminotransferase/alanine aminotransferase, alkaline phosphatase, γ-glutamyl transpeptidase, bilirubin, and prothrombin time were significantly improved after 7 days of abstinence. In the probiotics group (baseline and after), albumin (3.5±0.7 and 3.7±0.6 g/dl, P=0.038) and tumor necrosis factor-α (121±244 and 71±123 pg/ml, P=0.047) showed differences. In addition, the number of colony-forming units of Escherichia coli was significantly reduced (435±287 and 168±210, P=0.002). In the placebo group, the level of LPS (1.7±2.8 and 2.0±2.7 EU/ml) was significantly increased. In the intergroup comparison, significant differences in the levels of tumor necrosis factor-α (P=0.042) and LPS (P=0.028) were observed between the groups. Conclusion Immediate abstinence is the most important treatment for patients with AH. In addition, 7 days of oral supplementation with cultured L. subtilis/S. faecium was associated with restoration of bowel flora and improvement of LPS in patients with AH.